2018
DOI: 10.1111/pde.13392
|View full text |Cite|
|
Sign up to set email alerts
|

A comprehensive next‐generation sequencing assay for the diagnosis of epidermolysis bullosa

Abstract: EBSEQ is a sensitive, relatively rapid, minimally invasive, comprehensive genetic assay for the diagnosis of epidermolysis bullosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 67 publications
1
26
0
1
Order By: Relevance
“…Has et al elucidated 90% (36 of 40) of the studied cases by a NGS‐panel that included 49 genes . Finally, Lucky et al found an efficiency of 97.7% (42/43 patients) in an NGS assay that included 21 genes, in which all the identified mutations were present in only five genes ( KRT5 , KRT14 , LAMB3 , COL17A1 , COL7A1 ) . Therefore, our efficiency to detect the causative mutations was quite similar to that of other studies with larger panels.…”
Section: Discussionsupporting
confidence: 80%
“…Has et al elucidated 90% (36 of 40) of the studied cases by a NGS‐panel that included 49 genes . Finally, Lucky et al found an efficiency of 97.7% (42/43 patients) in an NGS assay that included 21 genes, in which all the identified mutations were present in only five genes ( KRT5 , KRT14 , LAMB3 , COL17A1 , COL7A1 ) . Therefore, our efficiency to detect the causative mutations was quite similar to that of other studies with larger panels.…”
Section: Discussionsupporting
confidence: 80%
“…Epidermolysis bullosa (EB) is a genetically heterogeneous group of inherited diseases, and causative mutations of EB have been identified in more than 20 genes. 5 DEB, a heterogeneous group of EB, is caused by COL7A1 mutation. As a distinct subtype of DEB, DEB-Pr is characterized by pruritus and prurigo-like lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor , Traditionally, the diagnosis of epidermolysis bullosa (EB) was made using electron microscopy (EM) and immunofluorescence mapping (IFM). Increasingly, genomics plays a role in EB diagnosis, and other genetic conditions, with a turn‐around time in as little as 1–3 weeks . The rapid turn‐around time and accuracy of genetic testing mandates a rethink on how we currently assess infants and children with EB.…”
Section: Patient Diagnosis Summary N (%)mentioning
confidence: 99%